DO ASIAN AND NON-ASIAN DIFFERENT? A COMPARATIVE STUDY OF SENIOR TOURISTS’ MOTIVATION WHEN TRAVELLING TO BALI - Serli Wijaya (Universitas Mercu Buana, 2019)
This research aimed to identify the push and pull factors of the motivation of senior tourists from Asia and non-Asia in choosing Bali as their destination, as well as examining any differences in the push and pull factors of both groups of nationality. Exploratory factor analysis that was continued with differences analysis were completed to analyse the data. Results revealed six factors that pushed seniors to travel to Bali: 1) exploring and increasing knowledge about the local culture, 2) quality time and visiting nostalgic places with close accompanies, 3) relaxation and having fun, 4) spending time with family members, 5) rejuvenation and health, 6) sharing about destination experience. In addition, there were four pull factors namely: 1) hospitality services and tourist attractions, 2) local culture, 3) natural scenery and climate, 4) quite rest area. While significant differences shown between Asian and non-Asian in factors that intrinsically pushed them totravel to Bali, no significant differences appeared between senior tourists from two groups of nationaliy in considering Bali’s destination attributes that pulled them to visit the island.